Bosonized Supersymmetric Sawada–Kotera Equations: Symmetries and Exact Solutions*Supported by the National Natural Science Foundation of China under Grant No. 11305031, the Natural Science Foundation of Guangdong Province under Grant No. S2013010011546, the Science and Technology Project Foundation of Zhongshan under Grant Nos. 2013A3FC0264 and 2013A3FC0334, and Training Programme Foundation for Outstanding Young Teachers in Higher Education Institutions of Guangdong Province under Grant No. Yq2013205. (1st April 2015) - Liu, Ping; Zeng, Bao-Qing; Liu, Li-Ming
Abstract The Bosonized Supersymmetric Sawada–Kotera (BSSK) system is constructed by applying bosonization method to a Supersymmetric Sawada–Kotera system in this paper. The symmetries on the BSSK equations are researched and the calculation shows that the BSSK equations are invariant under the scaling transformations, the space-time translations and Galilean boosts. The one-parameter invariant subgroups and the corresponding invariant solutions are researched for the BSSK equations. Four types of reduction equations and similarity solutions are proposed. Period Cnoidal wave solutions, dark solitary wave solutions and bright solitary wave solutions of the BSSK equations are demonstrated and some evolution curves of the exact solutions are figured out.